Basic logic - Domingo, Emmanuel R. (Quezon City, Philippines : Libro Filipino Enterprises, 2005)
The text consists of definitions, examples, comments and exercises. The comments contain materials we deem essential to the text. In this age of large classes and diminished persoal contact between students and their teachers, we hope this book promotes a rewarding learning experience.
Chapter 1 : The what and why og logic -- Chapter 2 : Simple apprehension, idea and term -- Chapter 3 :Predicables and predicament -- Chapter 4 : Definition and meaning -- Chapter 5 : Judgment and propositions -- Chapter 6 : Immediate inference - part 1 / Immediate inference (equivalence of propositions)- Part 2 -- Chapter 7 : Venn diagram and categorical proposiions -- Chapter 8 : Reasoning and argument / Categorical syllogism - part 2 / figures and moods of categorical syllogism - part 3 -- Chapter 9 : Compound syllogism -- Chapter 10 : Variations of syllogism -- Chapter 11 : Fallacies of reasoing -- Chapter 12 : Introduction to symbolic logic -- Chapter 12 : Introduction to symbolic logic -- Chapter 13 : Determining the validity of arguments -- Chapter 14 -- Formal proof of validity.
Includes bibliographical references.
Keywords: LOGIC